The evaluation of solution hazard criteria : a statistical approach to changes of selected soil physical properties under the influence of saline irrigations waters - Van Rooyen, Pieter Cornelis (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil. Agric.) -- University of Stellenbosch, 1973.